Impact of supply chain coordination on honey farmers' income in Tigray, Northern Ethiopia - Abebe Ejigu Alemu; Miet Maertens; Jozef Deckers; Hans Bauer; Erik Mathijs (Agricultural and Food Economics, 2016)
Most of the literature on vertical coordination and its impact on farm performance and farmer wellbeing deal with high-value or modern food supply chains, including export chains and chains dominated by large international supermarkets or other forms of foreign direct investment. The impact of vertical coordination mechanisms in local food supply chains in developing countries remains underexplored. This paper analyzes the impact of participation of honey producers in the Northern highlands of Tigray, Ethiopia in contracts and marketing cooperatives on their performance and wellbeing. The paper finds positive production and economic gains honey producers obtain from contract engagement. Honey producers under the contract scheme produce more white honey fulfilling the demand of processors, buyers and consumers. Contracting results in higher production due to the better access it causes to technology and skill transfers. Moreover, better conditions contracts offer motivates honey producers to produce more and supply larger to the market.
Keywords: Q13; 330; Supply chain coordination; Honey production; Ethiopia